Development of Load and Resistance Factors for Reinforced Concrete Structural Members in North Cyprus - Mahmud, Abdulhamid Sagir (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
Load and Resistance Factor Design (LRFD), is a widely used procedure in the design of reinforced concrete, wood and steel structures. It is a reliability-based procedure for design, which gives a framework that is consistent with civil engineering design codes, in accordance with reliability theories. In this study, Advance First Order Second Moment (AFOSM) approach is used as the reliability approach in carrying out the analysis. Uncertainties related to material properties (i.e. compressive strength of concrete, yield and ultimate strength of reinforcing steel bars.), dimensions of reinforced concrete structural members (beams and columns) and the effect of load variables (i.e. Dead and Live load), are considered. Under the framework of AFOSM the failure mode in different reinforced concrete structural members were analyzed, which focused mainly on flexure failure, shear failure and the combined action of flexure and axial load failure. Reliability indexes are calculated according to the flexure and shear failure modes in beams and columns, in addition to failure due to the combine action of flexure and axial load on columns. Target reliability indexes are selected for different load combinations from values reported by other researchers from different countries, which are used as the safety level to evaluate the computed reliability indexes. New load and resistance factors are selected for different failure modes in different structural members, considering the design practice in North Cyprus and specifications given in the Turkish codes (e.g. TS500). Keywords: Model Uncertainty, Reliability, LRFD, Reliability Index, Safety Level

Öz: Yük ve Dayanım Katsayılarına göre Tasarım (YDKT), betonarme, ahşap ve çelik yapı elemanlarının tasarımında yaygın olarak kullanılan bir yöntemdir. Bu yöntem güvenilirlik esasına dayanan, tasarım yönetmelikleri çerçevesinde ve güvenilirlik teorilerine uygun bir yöntemdir. Bu çalışmada analizler “Geiştirilmiş Birinci Mertebe İkinci Moment” (GBMİM) yaklaşımı ile yapılmıştır. Çalışma kapsamında malzeme özellikleri (beton basınç mukavemeti, beton çelik çubukları çekme dayanımı v.b), betonarme elemanların boyutları (kirişier ve kolonlar) ve yük değişkenlerinin etkisine (sabit ve hareketli yükler) ilişkin belirsizlikler dikkate alınmıştır. GBMİM yaklaşımı çerçevesinde farklı betonarme yapı elemeanlarının göçme durumu incelenmiştir. Bu çalışmada esas olarak eğilme, kesme ve eksenel kuvvet-eğilme etkileşimindeki elemanlar dikkate alınmıştır. Bu bağlamda betonarme kirişlerde eğilme ve kesme göçme durumları ile eksenel kuvvet ve eğilme etkisindeki betonarme kolonların “güvenilirlik indeksleri” hesaplanmıştır. Farklı yük birleşimlerine göre daha önceki çalışmalarda farklı ülkeler için rapor edilen hedef güvenilirlik indeksi değerleri seçilmiştir. Hesaplanan güvenilirlik indeksi seçilen hedef güvenilirlik indeksi ile kıyaslanarak yeterli güvenlik seviyesine ulaşılmıştır. Yapılan çalışma kapsamında Kuzey Kıbrıs’ta tasarım uygulamaları ve TS500’de belirtilen kurallar çerçevesinde yeni yük ve dayanım katsayıları belirlenmiştir. Anahtar Kelimeler: Belirsizlik Modeli, Güvenilirlik, YDKT, Güvenilirlik İndeksi, Güvenlik Seviyesi
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2017. Supervisor: Assoc. Prof. Dr. Serhan Şensoy.
Keywords: Civil Engineering; Reinforced concrete construction; Load and Resistance Factor Design (LRFD); Cyprus; Model Uncertainty; Reliability; LRFD; Reliability Index; Safety Level